Serogroup c meningococcal glycoconjugate vaccine in adolescents: persistence of bactericidal antibodies and kinetics of the immune response to a booster vaccine more than 3 years after immunization - Snape, M; Kelly, D; Salt, P; Green, S; Snowden, C; Diggle, L; Borkowski, A; Yu, L; Moxon, E; Pollard, A (University of Chicago Press, 2006)
Background. The persistence of protection from meningococcal disease following immunization with serogroup C meningococcal (MenC) glycoconjugate vaccines in infancy is short-lived. The duration of protective immunity afforded by these vaccines in other at-risk age groups (i.e., adolescents and young adults) is not known. We evaluated the persistence of bactericidal antibodies following immunization with a MenC glycoconjugate vaccine (MenCV) in adolescents and the kinetics of immune response to a meningococcal AC plain polysaccharide vaccine (MenPS) challenge or a repeat dose of MenCV. Methods. We conducted a randomized comparative trial of 274 healthy 13–15-year-olds from whom a total of 4 blood samples were obtained (prior to administration of a dose of MenPS or MenCV, again on 2 further occasions at varying times from days 2–7 after vaccination, and finally on day 28 after vaccination. The correlate of protection was a serum bactericidal assay titer ≥8 (with a serum bactericidal assay using human complement). Results. A serum bactericidal assay using human complement titer ≥8 was observed in 75% of participants at baseline (mean age, 14.5 years; mean time since routine MenCV vaccination, 3.7 years). No increase in serum bactericidal assay geometric mean titers was detected until day 5 after administration of MenPS. Geometric mean titers following administration of MenCV were significantly higher than those observed following administration of MenPS, at days 5, 7, and 28. Conclusions. This study showed sustained levels of bactericidal antibodies for at least 3 years after immunization of adolescents with MenCV. After challenge of immunized adolescents with MenPS, there was no increase in serum bactericidal assay observed until day 5 after vaccination, indicating that immunological memory may be too slow to generate protection against this potentially rapidly invasive organism.